Media Pembelajaran E-Modul Materi Sistem Pengapian berbasis Flipbook - Wijayanto, Didiek Wahyu; Leksono, Ibut Priono; Rusmawati, Retno Danu (Jurnal Pendidikan Edutama, 2022)
Abstract: The flipbook-based ignition system e-module is an electronic ignition system module which includes ignition system material whose material is equipped with pictures, video explanations of material and interactive quizzes that can be applied online using a smartphone or computer without having to download it first. This study aims to (1) produce an e-module ignition system material which was developed using flip pdf pro software whose end result is an e-module that can be accessed anywhere as long as internet access is available, (2) describe the feasibility level of the e-module validated by expert and peer and student trials. This type of research is Research & Development (R&D) with the adaptation of the Dick and Carey model using data collection instruments in the form of questionnaires and expert reviews, while the data analysis technique uses qualitative descriptive analysis techniques and descriptive statistical analysis. The results showed the feasibility of the product with the percentage figure above 85% (very feasible). Keywords: e-module, ignition system, flipbook, teaching materials  Abstrak: -modul sistem pengapian berbasis flipbook adalah modul elektronik sistem pengapaian yang didalamnya berupa materi sistem pengapaian yang materinya dilengkapi dengan gambar, video penjelasan materi  dan quiz interaktif yang dapat diaplikasikan secara online menggunakan smartphone maupun computer tanpa harus mendownload terlebih dahulu. Penelitian ini bertujuan untuk (1) menghasilakn e-modul materi system pengapian yang dikembangkan menggunakan software flip pdf pro yang hasil akhirnya adalah e-modul yang bisa diakses dimana saja selama tersedia akses internet, (2) mendiskripsikan tingkat kelayakan e-modul yang divalidasi oleh ahli dan uji coba teman sejawat dan siswa. Jenis penelitian Research & Development (R&D) dengan adaptasi model Dick and Carey dengan menggunakan instrument pengumpulan data berupa angket dan review ahli sedangkan teknik analisi data menggunakan teknik analisis deskritif kualitatif dan analisis statistic deskritif. Hasil penelitian menunjukan kelayakan produk dengan angka persentasenya diatas 85% (sangat layak). Kata Kunci: e-modul, system pengapian, flipbook, bahan ajar